Indonesian English: whats det tuh? - E. Aminudin Aziz (TEFLIN, 2003)
In a seminar on ESP held in Bandung, Andy Kirkpatrick of Curtin University of Technology, Australia, in relation to the anticipation of the potential emergence of a new variety of English in the Southeast Asian region and in Indonesia in particular, invited the audience, who were mostly university teachers, to start thinking about developing a teaching program based more on Indonesian culture than on, Anglo or American culture. This idea is based on the fact that Ã¢â¬Åthe vast majority of people in the region who are learning English are doing so with the expressed purpose of being able to use it as a lingua franca. They are not learning English to communicate with native speakers of English, but rather with other non-native speakersÃ¢â¬Â (Kirkpatrick 2001). While the idea is